Drying Characteristics Variation in Dry Pre-treated Seven and 10-Year-old Acacia mangium - Elia, Ambrose (University Malaysia Sarawak, 2022)
In Sarawak, Acacia mangium is the primary species used for commercial forest plantation to reduce timber dependency from the natural forest. The wood has adequate strength, quality and durability for appropriate utilization and end-use. However, the uneven distribution of moisture content and drying defects are the primary problems in converting Acacia mangium wood into high-value products. The major cause of those problems is the presence of wet pockets in the dried wood. The objectives of this study were to (1) determine the untreated moisture content and the physical properties of seven and 10-year-old of A. mangium wood, (2) determine the effect of pre-treatments on the drying time, occurrence of wet pocket and drying defects in dried A. mangium boards, and (3) develop new drying schedules for seven and 10-year-old A. mangium board. Trees of seven and 10-year-old A. mangium were obtained from a plantation. The felled trees were rough sawn to 50 mm and 400 cm thick and long, respectively. Defects-free quarter and rift-sawn sample boards were selected and subsequently cut to a standard size of 27 mm (thickness) × 150 mm (width) × 690 mm (length). Three pre-treatments experimented were incision, forced air drying and pressure. The average basic wood density of 10-year-old Acacia mangium was significantly higher than seven-year-old A. mangium. The untreated moisture content of the seven-year-old is greater than the 10-year-old A. mangium. Results showed that pressure pre-treatment was the best for both seven and 10- year-old A. mangium. All sample boards treated with pressure did not show severe drying defects such as checks, collapse, and honeycombing. Mild schedule was recommended for both seven and 10-year-old A. mangium. Although the recommended schedule is not the fastest in terms of drying rate, it can reduce the occurrence of wet pocket and minimize the incidence of drying defects in both ages. The newly developed drying schedule for seven-year-old A. mangium indicate that kiln drying begins with an initial dry-bulb temperature of 45 °C, the wet-bulb depression 1.7 °C and the final dry bulb temperature of 70 °C. For 10-year-old A. mangium begin with an initial dry-bulb temperature of 48 °C, wet-bulb depression 4.0 °C and the final dry bulb temperature of 71 °C. Application of the new drying schedule on flat sawn sample boards succeed with no severe drying defects. The new drying schedule for 10-year-old A. mangium able to reduce the occurrence of wet pocket